Verbal and nonverbal predictors of executive function in early childhood. Issue 2 (15th March 2018) - Stephens, Rebecca L.; Langworthy, Benjamin; Short, Sarah J.; Goldman, Barbara D.; Girault, Jessica B.; Fine, Jason P.; Reznick, J. Steven; Gilmore, John H.
ABSTRACT: The study of executive function (EF) has become increasingly popular in multiple areas of research. A wealth of evidence has supported the value of EF in shaping notable outcomes across typical and atypical development; however, little evidence has supported the cognitive contributors to early EF development. The current study used data from a large longitudinal sample of healthy children to investigate the differential influence of verbal and nonverbal cognition on later EF. Participants were assessed at 2 years of age using the Mullen Scales of Early Learning, and Mullen scores were used to calculate nonverbal and verbal developmental quotients. Executive function was measured at 6 years using assessments from the Stanford-Binet, Cambridge Neuropsychological Test Automated Battery, and the Behavior Rating Inventory of Executive Function. Results suggested that early nonverbal cognition was a better predictor of 6-year EF as measured by task-based laboratory assessments, whereas verbal cognition was a better predictor of parent-reported EF. Findings are discussed in regard to EF development and characteristics of EF measurement.